Development of Ultrasonic Modulation Probe for Fluorescence Tomography Based on Acousto-Optic Effect - Trinh Quang Duc; Shunsuke Kaneta; Masaki Kobayashi (International Journal of Optics)
We have developed an ultrasonic probe for fluorescence modulation to image fluorescence within biological tissues. The probe consists of a focused ultrasonic transducer mounted on actuators for mechanical fan scanning, which can be used in contact with the measuring object aiming for clinical application. The mechanical fan scanning employed in the probe has a beneficial feature of portability. As a result, fluorescent beads, which were localized with the diameter of 2 mm at 20 mm depth in a pork meat tissue, were detected with resolution of 3 mm. The system performance denotes the feasibility of development towards the final goal of ultrasonic fluorescence modulation tomography for clinical applications.